Stationary parameters of a retrial queueing system with a T-returns of customers under a first come, first served discipline - Коба, О. В. (Proceedings of National Aviation University (archive), 2003)
Generalizing a model introduced by L.Lakatos, the author considers a GI/G/l retrial queueing system in which orbit cycles of customers equal a constant T and a FIFO (first come, first out) queueing discipline is fulfilled. If a service time does not exceed T then a steady-state distribution of an imbedded Markov chain is obtained. Mean number of customers in the orbit is derived